Analisis Kebutuhan Media Pembelajaran Berbasis FlipHTML5 Materi Sejarah Lokal Pantai Timur Sumatera Selatan di MAN 1 Ogan Ilir - Kaka Picasso Destani; Farida R. Wargadalem (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to conduct an in-depth analysis of students’ needs regarding the use of FlipHTML5-based learning media in teaching Local History of the East Coast of South Sumatra at MAN 1 Ogan Ilir. The study employs a descriptive quantitative approach that focuses on depicting the actual conditions of classroom learning. Data were collected through the distribution of questionnaires to 70 tenth-grade students as research respondents. The results indicate that 95,7% of students stated that they were able to understand the material delivered by the teacher relatively easily using the learning methods that have been implemented so far. However, 92,9% of students reported that they still require additional explanations and more varied exercises to achieve optimal understanding of the material. Furthermore, 91,4% of students stated that local history material is important to learn because it is directly related to their environment and regional identity. In addition, 94,3% of students agreed that history learning would be more engaging and less monotonous if supported by interactive digital media. Based on these findings, it can be concluded that the development of FlipHTML5-based learning media is highly relevant to students’ needs and has the potential to enhance the quality and attractiveness of local history learning in schools.